LRFD Aid for Tubeshaped Beams - Siddiqui, Faruq M.A.; Usman, Ali (Engineering Journal, 1990)
In a previous issue of the Engineering Journal, the first author presented beam design aids in the form of an "economic section" table for laterally supported standard tubeshaped beams designed according to the 1978 AISC Specifications. The authors feel that with the increasing use of the 1986 AISC LRFD Specifications, a table similar in scope and content but using the LRFD specifications would be highly desirable. The accompanying tables would greatly facilitate the selection of tubular flexural members and would complement the existing beam design aids available for other rolled shapes in the LRFD manual.The design aid information available here is valid for tubular sections used as beams. It is assumed that the loading is applied in the plane of the minor axis and that the beam deflects vertically in the plane of bending only. This paper uses the same nomenclature as the LRFD manual.